2017
DOI: 10.1007/s12035-017-0791-0
|View full text |Cite
|
Sign up to set email alerts
|

Fifty-Hertz Magnetic Field Affects the Epigenetic Modulation of the miR-34b/c in Neuronal Cells

Abstract: The exposure to extremely low-frequency magnetic fields (ELF-MFs) has been associated to increased risk of neurodegenerative diseases, although the underlying molecular mechanisms are still undefined. Since epigenetic modulation has been recently encountered among the key events leading to neuronal degeneration, we here aimed at assessing if the control of gene expression mediated by miRNAs, namely miRs-34, has any roles in driving neuronal cell response to 50-Hz (1 mT) magnetic field in vitro. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 91 publications
(141 reference statements)
2
64
0
2
Order By: Relevance
“…SH‐SY5Y neuroblastoma cells can be differentiated toward a dopaminergic phenotype when administered with RA‐PMA, as previously characterized [Benassi et al, ; Consales et al, ]. As shown in Figure , all the sequences analyzed in differentiated SH‐SY5Y cells showed a strong statistically significant difference in the 5‐mC percentage compared to the proliferating counterpart.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…SH‐SY5Y neuroblastoma cells can be differentiated toward a dopaminergic phenotype when administered with RA‐PMA, as previously characterized [Benassi et al, ; Consales et al, ]. As shown in Figure , all the sequences analyzed in differentiated SH‐SY5Y cells showed a strong statistically significant difference in the 5‐mC percentage compared to the proliferating counterpart.…”
Section: Resultssupporting
confidence: 71%
“…The extent of global DNA methylation and its possible changes do not necessarily overlap with DNA methylation changes occurring at gene‐specific promoters [Sharma et al, ; Öner et al, ]. Indeed, we recently reported that ELF‐MFs (applied to both proliferating and differentiated SH‐SY5Y under the same experimental conditions used in this study) trigger hypermethylation of the miR‐34b/c promoter [Consales et al, ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Furthermore, these effects appear under exposure to much weaker magnetic fields, on the level of several milliTeslas (mT) which present no cytotoxic or genotoxic effects (Boorman et al 1997;Pettenati et al 2018). There is already growing concern about the effects of exposure to ELF MFs as epidemiological (Davanipour et al 2007;Zhou et al 2012) and experimental (Consales et al 2012(Consales et al , 2018 findings point to possible associations with neurodegenerative diseases. However, efforts are being made to identify useful effects under controlled exposure conditions.…”
Section: Introductionmentioning
confidence: 99%